Neuroendocrine tumor of the gastrointestinal: report of two cases - Made Agus Dwianthara Sueta; Made Oka Sastrawan (DiscoverSys Inc., 2019)
Introduction: Neuroendocrine tumors are malignancies that need special attention because they provide clinical manifestations that are not typical of excess gastrointestinal endocrine production. Case reports of neuroendocrine tumors are needed to be able to recognize the symptoms and determine the appropriate therapy.Case series: The first patient was 49 years old Balinese female, consulted from internist with right lower-quadrant tenderness with fever for three days before. The patient also had diarrhea for one week before. The patient has done an appendectomy, and the pathological result of the appendix specimen was Neuroendocrine Appendix. The second patient was 62 years old Balinese male, complained about intermittent diarrhea for two months. Patient has done laparotomy exploration and colostomy because of a transverse colon tumor. The pathological result of the specimen from transverse colon tumor was mixed adeno-neuroendocrine carcinoma. Both patients have been treating with hormonal therapy (somatostatin analogs) long-acting release (LAR); the second patient also had combined with folfox IV chemotherapy.Conclusion: The choice of therapy with somatostatin analogs in the first case and surgery in the second case gave a good response after treatment. However, in both cases, it does not guarantee the cure of this disease.Â